2017
DOI: 10.1111/avsc.12324
|View full text |Cite
|
Sign up to set email alerts
|

Changes in floristic composition and physiognomy are decoupled along elevation gradients in central Argentina

Abstract: Questions Most vegetation descriptions tacitly assume that floristic composition and physiognomy are tightly linked. However, the two vegetation properties may not respond in a similar way to environmental and disturbance gradients, leading to uninformed management planning and difficulties when attempting to restore degraded ecosystems. In this context, we addressed two main questions: (1) how close are relations between floristic and physiognomic types as defined by numerical vegetation classification in mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1
38

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 72 publications
(139 reference statements)
5
75
1
38
Order By: Relevance
“…Species richness was higher in HF than in LF. This pattern is common in many ecosystems of the world, particularly in dry Mediterranean woodlands (Bond & van Wilgen, 1996;Giorgis et al, 2013Giorgis et al, , 2017Guo, 2001), where richness was found to increase mainly in the first decade after the recurrent fires and to decrease when the forest canopy began to close (Tessler, Wittenberg, & Greenbaum, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Species richness was higher in HF than in LF. This pattern is common in many ecosystems of the world, particularly in dry Mediterranean woodlands (Bond & van Wilgen, 1996;Giorgis et al, 2013Giorgis et al, , 2017Guo, 2001), where richness was found to increase mainly in the first decade after the recurrent fires and to decrease when the forest canopy began to close (Tessler, Wittenberg, & Greenbaum, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Woody native species have been found to support fires through different mechanisms: Small or young individuals can resprout from the base, whereas large or mature individuals are more susceptible to fire, but they can escape from fires occurring at the understory level (Gurvich et al, 2005). The pristine condition of the region is still not very well understood (Giorgis et al, 2017). Nonetheless, simulations showed that the region could have been almost completely covered by dry forest (Cingolani, Renison, Tecco, Gurvich, & Cabido, 2008).…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…, ; Giorgis et al . ). The alien shrub Cotoneaster franchetii (Rosaceae, Maloideae) spreads markedly in the region (Tecco ; Giorgis et al .…”
Section: Methodsmentioning
confidence: 97%
“…The dominant vegetation includes Lithraea molleoides, Schinopsis marginata and other woody species in the forests, Vachellia caven (ex Acacia caven ) in the shrublands and Festuca hieronimy in the grasslands ( see Giorgis et al . and Cabido et al . for full description of the floristic and physiognomic classification of the ecosystem).…”
Section: Methodsmentioning
confidence: 87%
“…), fire, grazing and the recent advance of woody exotic species are the major drivers of vegetation change in the mountains of the region, transforming the landscape into a complex mosaic of degraded native forests, monospecific stands of woody exotics, shrublands and grasslands (Hoyos et al ; Giorgis et al . , , ; Furey et al . ; Zeballos et al .…”
Section: Methodsmentioning
confidence: 99%